Geothermal System as the Cause of the 1979 Landslide Tsunami in Lembata Island, Indonesia - Yudhicara, Yudhicara; Bani, Phillipson; Darmawan, Alwin (Geological Agency, 2015)
DOI:10.17014/ijog.2.2.91-99A tsunami landslide which caused hundreds casualties and lots of damage took place on Lembata Island in 1979. In order to understand the characteristics of the landslide mechanism, a field survey was conducted in 2013 which sampled both the origin soil and landslide material, and the water from hotspring around the landslide site. The physical properties of the soil obtained show that the original soil has dominantly coarser grain than the landslide material (80.5% coarser grain compared to 11.8% coarse grain respectively) which indicates that the soil has become finer and softer. Hot spring analysis indicated that the mineral content of the water was 99.48% SO4. This shows that magmatism processes are involved which caused the soil to become acidic and may have fragilised the system. Results of X-ray Diffraction Mineralogy Analysis (XRD) show that the original soil is composed of minerals of cristobalite, quartz, and albite, while the landslide material consists of clay minerals such as quartz, saponite, chabazite, silicon oxide, and coesite which are typical minerals in a hydrothermal environment. Based on these results, it can be concluded that the area was influenced by an active geothermal system that could be the main source mechanism behind this disastrous event.Â